Letter - Picken, M.
1943-10-15 038-0019-001 ALL COMMUNICATIONS TO BE ADDRESSED TO THE [GENERAL] SECRETARY NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND BASQUE CHILDREN'S TRUST LTD. PRESIDENT: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. CHAIRMAN: MISS ELEANOR RATHBONE, M.P. VICE-CHAIRMAN: THE EARL OF LISTOWEL. HON. SECRETARIES: LADY LAYTON Mr. D.R. GRENFELL, M.P. Mr. WILFRID ROBERTS, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. HON. APPEALS SECRETARY: Mrs. V.E. MILLER SECRETARY: MISS M. PICKEN. 39, VICTORIA STREET, LONDON, S.W.1. TELEPHONE: ABBEY 7463 October 15th, 1943. Ref. WMC/FEM/MMC/79 Dear Sir, I am writing on behalf of our President to thank you for your letter of October 13th, and for your kindness in informing her that her appeal for help to carry on the work for the Basque children will be placed before the General Council at their next meeting. Yours very truly, M Picken Secretary. Sir Walter Citrine., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/38/19(I)